Inflation-Output Efficiency in Lowering High Cost Economy: A Comparative Study of Several Provinces in Indonesia - Gitaharie, Beta Y.; Mardanugraha, Eugenia; Nuryakin, Chaikal (Economics and Finance in Indonesia, 2007)
.